Flow Cytometric Pattern of TCRVδ Subtype Expression Rapidly Identifies γδT Cell Lymphoma - Chen, Xiao; Zhao, Sishu; Liu, Lu; Qiao, Chun; Wang, Yan; Fan, Lei; Jin, Huimin; Wu, Yujie (Frontiers in Oncology, 2020)
γδT cell lymphoma (γδ TCL) is a class of hematopoietic malignancy that express the γδ T-cell receptor (TCR) with a low incidence. Determining the clonal proliferation of γδT cells is important for the diagnosis of such malignancies. Few studies have used flow cytometry to detect VδTCR and its subtypes (Vδ1 and Vδ2) at the protein level, although it is a practical method for determining the clonality of γδT cells. A TCRVδ-based 10-color protocol was designed for the detection of monoclonal proliferation of γδT subtype cells by multiparameter flow cytometry, and the diagnostic results were compared with gene rearrangement results.All 19 cases of γδ TCL were positive for cluster of differentiation 3 (CD3) and TCR γδ and presented with abnormal distribution patterns of Vδ1 and Vδ2, of which 16 of the 19 cases showed restricted Vδ1 staining pattern and the remaining 3 cases lacked expression of either Vδ1 or Vδ2. Among the 10 normal controls and 11 patients with reactively higher CD4 and CD8 double-negative ratio, the percentage of Vδ2 positive events (range: 16.4%–99.0%) was significantly higher than that of Vδ1 (range: 0%–50.5%; p<0.0001), and all cases had a normal Vδ distribution pattern. To detect clonality, there was no difference in the detection rate between TCRVδ analysis and gene scanning techniques (p =1.000) with a high degree of coincidence (Kappa = 0.850, p < 0.001). Heteroduplex analysis was less sensitive than the other methods but was more speciﬁc (100%) than the gene scanning techniques, and TCRVδ subtype analysis had the highest sensitivity, speciﬁcity, positive predictive value(PPV), and negative predictive value(NPV). Compared with molecular methods, immunophenotyping are able to distinguish the T cell lineage. The γδT panel based on the TCRVδ antibody by flow cytometry could be advantageous for the rapid identification of suspected γδTCL.